ANALISIS AKAD TANGGUNG RENTENG DALAM PERSPEKTIF MUAMALAH SYARIAH DI BADAN USAHA MILIK DESA BERSAMA SINGOLESTARI KECAMATAN SINGOJURUH - Ficky Septalinda; Restu Cahya Ningrum (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2021)
This study explains the joint responsibility transactions that exist within the Joint Village Owned Enterprise (BUMDesma) Singolestari, Singojuruh sub-district. Where BUMDesma is an interesting thing to study, namely the joint responsibility system used in settling bad loans. The formulation of the problem in this research is the practice of joint responsibility and joint responsibility system in the Islamic perspective. This study uses a qualitative descriptive method with a phenomenological approach. From the results of field research, it is found that in practice the joint responsibility transaction in BUMDesma is a dependent if one of the members cannot pay at maturity by dividing the deposit amount by the number of existing members. Based on the concept, the transaction system of joint responsibility is in accordance with the kafalah contract with the type of kafalah bil-maal, which is an obligation carried out by the guarantor with payment in the form of property or money and has fulfilled the requirements and pillars of the kafalah contract. The rules for joint responsibility in BUMDesma have been written in the proposal which is clearly made and has been approved by the customer in taking credit. However, in the savings and loan program which is not in accordance with the perspective of Islamic economics, namely taking profits from savings and loans is still in the percentage of INTEREST.